EFEK AROMATERAPI LILIN KOPI DAN SERAI: LITERATUR REVIEW - Vani, Ade Teti; Nadia Purnama Dewi; Dessy Abdullah; Rinita Amelia (Yayasan Nusantara Hasana Berdikari, 2024)
This research highlights a literature study on the health effects of aroma therapy candles made from coffee and lemongrass. Therapeutic aroma candles made from natural ingredients such as coffee and lemongrass are gaining popularity as they are believed to provide health benefits, such as reducing stress, promoting relaxation, and improving mood. The essential oils contained in coffee and lemongrass aroma therapy candles have active compounds that can affect the nervous and psychological systems. This study aims to assess the potential health benefits of using coffee and lemongrass aroma therapy candles based on existing literature studies.